KAJIAN PSIKOLOGI SASTRA DALAM NOVEL TOPI HAMDAN KARYA AUNI FA - Missriani; Yanti, Asri; Agustina, Juaidah (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2022)
Literary psychology is a field of study that examines literary works considered to reflect psychological processes and activities. This research questions how the intrinsic elements in the novel "Topi Hamdan" by Auni Fa can be examined in the context of literary psychology, and the purpose of this research is to describe the intrinsic elements and emotional classification of the characters in the novel. The method used is qualitative descriptive research, with data derived from the novel "Topi Hamdan" published by PT Tiga Serangkai Pustaka Mandiri in November 2017. In this study, data collection techniques used include literature review, reading techniques, and note-taking techniques. The literature review was conducted by collecting books and journals related to literary psychology. To ensure data validity, the technique of triangulation was used by comparing the theories and data collected by the investigator. The data analysis technique used is content analysis. Based on the research findings, it was found that the intrinsic elements in the novel "Topi Hamdan" by Auni Fa discuss Hamdan's life journey filled with problems and sadness. This research also examines the setting, atmosphere, time, and character portrayal in the novel. In the novel "Topi Hamdan" by Auni Fa, there are twenty characters who play competent roles. This research also classifies the emotions of the characters in the novel. The identified emotions include the concept of guilt, suppressed guilt, self-punishment, shame, sadness, hatred, and love.